Implication of Bcl-2-associated athanogene 3 in fibroblast growth factor-2-mediated epithelial–mesenchymal transition in renal epithelial cells. (May 2015) - Du, Feng; Li, Si; Wang, Tian; Zhang, Hai-Yan; Li, De-Tian; Du, Zhen-Xian; Wang, Hua-Qin
The epithelial–mesenchymal transition (EMT) of tubular epithelial cells to myofibroblast-like cells plays a substantial role in renal tubulointerstitial fibrosis, which is a common pathological character of end-stage renal disease (ESRD). Fibroblast growth factor-2 (FGF-2) triggers EMT in tubular epithelial cells and increases Bcl-2-associated athanogene 3 (BAG3) expression in neural progenitor and neuroblastoma cells. In addition, a novel role of regulation of EMT has been ascribed to BAG3 recently. These previous reports urged us to study the potential involvement of BAG3 in EMT triggered by FGF-2 in renal tubular epithelial cells. The current study found that FGF-2 induced EMT, simultaneously increased BAG3 expression in human kidney 2 (HK2) cells. Although FGF-2 induced EMT in nontransfected or scramble short hairpin RNA (shRNA) transfected HK2 cells, it was ineffective in BAG3-silenced cells, indicating a favorable role of BAG3 in EMT of tubular cells induced by FGF-2. Knockdown of BAG3 also significantly suppressed motion and invasion of HK2 cells mediated by FGF-2. Furthermore, we confirmed that BAG3 was upregulated in kidney of unilateral ureteral obstruction (UUO) rats, a well-established renal fibrosis model, in which EMT is supposed to exert a substantial influence on renal fibrosis. Importantly, upregulation of BAG3 was limited to tubular epithelial cells. Results of the current study identify BAG3 as a potential player in EMT of tubular epithelial cells, as well as renal fibrosis.